Pregnant Women's Knowledge Level About the Importance of Nutrition in the First Trimester of Sigodang Village, Simalungun Regency - Tati Adriana Saragih; Rovina Efranti Barus (Cattleya Darmaya Fortuna, 2025)
Pregnant women are a group that is quite nutritionally prone. Pregnant women have different food needs because there is a fetus growing in her. Malnutrition in pregnant women can affect the fetal growth process and can lead to miscarriage, abortion, stillbirth, neonatal death, congenital defects, anemia in the baby, intra-partum asphyxia (death in the womb), birth with low birth weight. The research design used is Descriptive using primary data through the distribution of questionnaires with the subject of the study being all pregnant women in Nagori tiga Balata, Kec. Jorlang Hataran Regency Simalungun in 2012 as many as 25 respondents. Based on the results of the study, it was found that not all pregnant women knew about the importance of nutrition in the first trimester. Based on the level of knowledge, the majority of mothers were less knowledgeable, namely 11 people (44%), based on the age of the majority of less knowledgeable mothers at the age of < 20 years, namely 6 people (24%), based on education, the majority of mothers with elementary education were 5 people (20%), based on the parity of the majority of mothers with low knowledge of primigravida, namely 5 people (20%), based on information sources, the majority of knowledge is less knowledgeable in mothers who obtain information sources from health workers, namely 5 people (20%). Based on research, it is recommended for health workers to improve their performance in providing counseling and health education to pregnant women and the community.